IMPLEMENTATION OF EDUCATION ADDRESSING CLIMATE CHANGE IN INDEPENDENT CURRICULUM FOR TEACHERS - Zahra, Siti Fatimah; Nikensari , Sri Indah; Rabbaniyah, Lathiefah; Nurjanah, Siti (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2025)
Climate change is a global challenge that impacts various aspects of life, including the education sector. Therefore, teachers play a strategic role in conveying the concepts of climate change mitigation and adaptation to students. This training aims to improve teachers' skills, particularly in understanding climate change prevention strategies that can be implemented in schools. The activity was conducted offline using a lecture method with presenters from within and outside the country. It was attended by teachers from various schools in Jakarta and the surrounding area, allowing participants to directly engage in active discussions with the speakers and other participants. The training's outcomes include improving teachers' understanding of the basic concepts of climate change and mitigation strategies that can be applied in everyday life, encouraging the implementation of environmentally-based learning practices in schools through ongoing mentoring, and developing networks between teachers and educators. This will undoubtedly be even more effective with the support of school facilities and the development of an appropriate curriculum.